Tingkat Keterbacaan Bahan Ajar Flexible Learning Berbasis Kolaboratif Saintifik - Septiana Dwi Utami; Ika Nurani Dewi; Ismail Efendi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
This study was conducted with the aim of analyzing the readability of scientific collaborative-based flexible learning teaching materials that acquire students' collaboration skills in maintaining environmental balance. The concept under study is limited to the basic competence of the interaction of living things and the environment. This type of research is development using 4D models (define, design, develop, and disseminate). The data collection technique in this study was a reading and note-taking technique. The readability instrument was measured using the Fry graph formula and the reader's understanding response questionnaire. Data were analyzed by descriptive technique. The results of the analysis of the readability scores showed that the teaching materials were at level 9 or higher than the level of readers who were still at level 7. The responses of students' understanding on aspects of format and appearance, use of terms and descriptions of content, and understanding of images were in the minimally moderate category. Thus, the teaching materials developed have good readability and are suitable to be used as teaching materials for science learning in junior high schools on the interaction of living things with the environment, especially in class IX.